Fundamental study on producing a favorable ionic mobility of PVA blends in cellulose-based polymer electrolytes via electrochemical analysis - Ahmad Salihin, Samsudin; Izan Izwan, Misnon; Saifful Kamaluddin, Muzakir; Mohd Ikmar Nizam, Mohamad Isa; Mohd Fakhrul Zamani, Abdul Kadir (2019)
In present work, polymer blend carboxymethyl cellulose (CMC)-polyvinyl alcohol (PVA) based biopolymer electrolyte incorporated with various amount of ammonium bromide (NH4Br) at room temperature is reported. The electrolyte films comprise CMC-PVA which acts as host polymer and NH4Br as proton provider were successfully prepared via casting technique. The interaction between host polymer and dopant salt were confirmed via Fourier Transform Infrared Spectroscopy (FTIR) analysis where there is shifting and intensity of the peak observed. The X-ray Diffraction analysis has proved the amorphousness of the sample when more NH4Br up to AB20 was introduced into the system. The thermal properties of solid biopolymer electrolytes (SBEs) were studied using Thermo Gravimetric Analysis (TGA) and Differential Scanning Calorimetry (DSC). It was observed in TGA that the decomposition temperature (Td) increased which indicates the improvement in thermal stability of biopolymer electrolytes. While in DCS analysis, the glass transition temperature (Tg) decreased as well as NH4Br concentration increased. The optimum room temperature ionic conductivity of 3.21 x 10-4 S cm-1 was achieved when 20 wt. % of NH4Br was introduced into the system. The temperature dependence of all the SBEs were discovered obeys to Arrhenius behavior where the regression value almost unity (R2 ~ 1). The increment of NH4Br leads activation energy of CMC-PVA-NH4Br system to decrease. The dielectric behavior has been carried out using dielectric permittivity and electrical modulus spectra. The transport properties of SBEs was investigated via deconvoluted FTIR and Electrical Impedance Spectroscopy (EIS) fitting analysis approach. Both of the method revealed the ionic conductivity of CMC-PVA-NH4Br based biopolymer electrolyte is primarily influenced by the ionic mobility and ions diffusion coefficient. The dc polarization method has been used to estimate the Transference Number Measurement (TNM) of mobile ions and has found the tion to be 0.99 for sample with highest ionic conductivity. The non-blocking reversible electrode was used in present work to identify the proton (H+) transference number which is observed the tH+ value of 0.31. subsequently, indicates that the conducting species are predominantly due to cationic conduction. The electrochemical potential window of the most conducting biopolymer electrolyte is up to 1.55 V. The specific capacitance (Csp) of CMC-PVA-20 wt. % NH4Br biopolymer electrolyte was calculated from Cyclic Voltammetry (CV) curve and the results shows good agreement with Csp obtained from Galvanostatic Charge-Discharge (GCD). The average value of power density and energy density was observed to be at ~1.94 kW kg-1 and ~3.05 Wh kg-1, respectively. The work finding on biopolymer electrolyte-based CMC-PVA-NH4Br system is considered has potential to be applied in energy storage devices.